1985
DOI: 10.1136/bmj.291.6511.1768-a
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyhemoglobin concentrations in smokers of sheesha and cigarettes in Saudi Arabia.

Abstract: dominant fingers, or the sharp edge of the opened base injures the palmar aspect of the non-dominant fingers if the base is held too close to the unprotected edge. Thus the dorsal aspects of the dominant fingers and the palmar aspects of the non-dominant fingers will be selectively at risk when opening a corned beef can, while injuries from other types ofcan are random. Corned beefis almost uniformly sold in tapered, key opened cans, the design of which is over 100 years old. These cans were originally chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
2
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 3 publications
4
54
2
3
Order By: Relevance
“…Another explanation of the difference in levels of ECO might be previous findings showing that waterpipe use is associated with greater CO exposure than cigarette use [29]. Other studies also had results similar to ours, showing that a waterpipe smoker was found to likely emit as much CO as 7, 8 or even 10 cigarette smokers [19,30,31]. On another hand, although CO has been shown to vary with age [32][33][34][35] and exposure to combustion of petroleum (β = 6.03) exhaled higher levels of carbon monoxide.…”
Section: Ijomeh 2014;27(4)supporting
confidence: 62%
“…Another explanation of the difference in levels of ECO might be previous findings showing that waterpipe use is associated with greater CO exposure than cigarette use [29]. Other studies also had results similar to ours, showing that a waterpipe smoker was found to likely emit as much CO as 7, 8 or even 10 cigarette smokers [19,30,31]. On another hand, although CO has been shown to vary with age [32][33][34][35] and exposure to combustion of petroleum (β = 6.03) exhaled higher levels of carbon monoxide.…”
Section: Ijomeh 2014;27(4)supporting
confidence: 62%
“…A study of habitual water-pipe smokers in Saudi Arabia found them to have a mean COHb level of 10.06% (SD 2.50%) compared with 1.60% (SD 0.20%) for nonsmokers and 6.47% (SD 2.73%) for cigarette smokers. 9 In contrast, our study demonstrated an acute rise in COHb levels in a single smoking session under controlled conditions.…”
Section: Discussioncontrasting
confidence: 48%
“…It has also been found that, of 14.7 mg of metals contained in 1 gm of jurak paste, only 3.1 μg was transferred to the inhalant smoke. This indicates that the water in the sheesha reservoir does retain some of the organic and metallic inhalants by acting as a solvent and a condensation medium, and thus the carcinogenic effect of the metallic compounds in jurak smoke is reduced.In an assessment of the risk factors prevalent among Saudi citizens for smoking-related diseases, serum levels of carboxyhemoglobin among jurak smokers were found to be significantly higher than those in cigarette smokers and nonsmokers [4,5]. Zahran et al [4,5,] attributed this finding to the carbon monoxide produced from jurak and charcoal.…”
mentioning
confidence: 91%